Digital Infrastructure, New Digital Infrastructure, and Urban Carbon Emissions: Evidence from China - Jiayun Nie; Jia Shen; Xiaohong Ren (Atmosphere)
To advance the global sustainable development agenda and uphold the emission reduction commitments of the Paris Agreement, this study is dedicated to exploring the potential of digital infrastructure construction in fostering carbon emission reductions. Drawing on panel data from 249 cities in China spanning the period from 2010 to 2021, we empirically analyze the impact, mechanisms, and heterogeneous effects of digital infrastructure construction on urban carbon emissions using a two-way fixed-effect model. Furthermore, we delve into the carbon-reducing effects of new-type digital infrastructure construction. The research findings indicate that digital infrastructure construction can significantly decrease urban carbon emissions; it achieves this by enhancing urban green innovation and heightening public environmental awareness, thereby further reducing urban carbon emissions. In city samples located in western regions, with higher government fiscal expenditures and better foundations for new energy utilization, the promotional effect of digital infrastructure construction on urban carbon emission reductions is more pronounced. Additionally, new-type digital infrastructure construction demonstrates a significant reduction in urban carbon emissions, and where new-type digital infrastructure is well developed, the carbon-reducing effect of digital infrastructure is even more evident. This study deepens our understanding of the mechanisms through which digitization empowers carbon emission reductions and the regional variations involved, providing empirical evidence for governments to formulate differentiated policies on digital infrastructure construction and carbon emission reductions. In future research, we plan to expand the scope of our investigation to more countries and regions globally; concurrently, we will conduct an in-depth analysis of the long-term effects of digital infrastructure construction on carbon emissions.